2021
DOI: 10.1590/s1678-9946202163055
|View full text |Cite
|
Sign up to set email alerts
|

Association of TAP1 1177A>G and 2090A>G gene polymorphisms with latent tuberculosis infections in sheltered populations, in the metropolitan area of Guadalajara, Mexico: a pilot study

Abstract: This is an open-access article distributed under the terms of the Creative Commons Attribution License.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…When single SNPs were analysed, the genotype frequencies for rs1057141‐CC of TAP1 were different between the CHC and control groups, although this difference was not significant after Bonferroni correction. Other studies have also observed that rs1057141‐C is associated with bacterial infections such as tuberculosis (Cazarez‐Navarro et al., 2021; Naderi et al., 2016; Wang et al., 2012; Zhang et al., 2021) and leprosy (Shinde et al., 2013). No significant differences in allelic and genotypic frequencies were observed for the other SNPs in this study.…”
Section: Discussionmentioning
confidence: 93%
“…When single SNPs were analysed, the genotype frequencies for rs1057141‐CC of TAP1 were different between the CHC and control groups, although this difference was not significant after Bonferroni correction. Other studies have also observed that rs1057141‐C is associated with bacterial infections such as tuberculosis (Cazarez‐Navarro et al., 2021; Naderi et al., 2016; Wang et al., 2012; Zhang et al., 2021) and leprosy (Shinde et al., 2013). No significant differences in allelic and genotypic frequencies were observed for the other SNPs in this study.…”
Section: Discussionmentioning
confidence: 93%
“… 26 Wang et al reported that rs1135216-C was significantly associated with the risk of TB in Li people in China. 27 Roh et al reported that TAP1 rs1057141 and rs1135216 SNPs were associated with susceptibility to active TB. 28 Naderi et al reported that the rs1135216-C allele was associated with an increased risk of PTB ( P <0.001, OR=2.65, 95% CI=1.784–3.969).…”
Section: Discussionmentioning
confidence: 99%
“…25 Some studies have shown that TAP gene polymorphisms are associated with TB in some populations. [26][27][28][29][30][31] In the present study, we analyzed the association between TB and TAP gene polymorphisms in a Han population in China. Previous studies revealed that the genetic effect could be affected by age, sex and family income.…”
Section: Introductionmentioning
confidence: 99%
“…In the Mexican population, the G allele and the GG genotype of rs1135216 of transporter associated with Ag processing ( TAP1 ) were associated with susceptibility to TBI [ 198 ].…”
Section: Evaluation Of Host-derived Biomarkersmentioning
confidence: 99%